PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID-19 DI PAUD MAWAR DI BANDUNG - Yuliany Yuliany (Fakultas Agama Islam Universitas Wiralodra, 2021)
This article aims to explore the implementation of Islamic Religious Education learning during the Covid-19 pandemic. This study uses a case study method with the aim of obtaining data related to the implementation of Islamic Religious Education learning during the Covid-19 pandemic. The results showed that learning at home with the habituation method was not as easy as imagined. The lack of enthusiasm for children and the lack of ability of parents in accompanying children are challenges in applying the habituation method. The principal of PAUD Mawar conveyed to the author that not all parents are like teachers at school. Many parents are not patient, children are usually shouted at which also has a bad effect. Maybe because of the circumstances, the child becomes less enthusiastic and bored, has no friends, and no one motivates.